Problematik Akta Perdamaian Pada Penyelesaian Sengketa Keperdataan Melalui Mediasi - Sulistianingsih, Dewi; Fibriani, Indira (Universitas Negeri Surabaya, 2023)
The purpose of this paper is to describe and analyze the settlement of civil disputes through mediation. Mediation is a dispute resolution process that is faster and cheaper, and provides access to the parties to resolve disputes. This paper is based on research conducted using library research. the approach used is a conceptual approach. The results in mediation are decisions that are expected to satisfy the parties so that in the future it can be carried out properly by the disputing parties. The dispute resolution process through mediation is assisted by a mediator. The mediation peace deed is made as a sign of the end of the dispute and the disputing parties have agreed to make peace and are binding on the disputing parties. The legal force between the results of mediation in court and the settlement of civil disputes through mediation is the same, namely permanent legal force. The legal consequences if the parties or one of the parties do not want to carry out the mediation peace deed, the trial can be continued. Settlement of disputes by means of Mediation in dispute resolution outside the court can produce efficient decisions, fast resolutions, the resulting decisions are satisfactory, and aim to resolve conflicts between the parties